A few uncertain pages of the (pre)history of labrets in Africa, and the questions they raise about the archaeological visibility of the wearing of lip adornments - (:unkn) unknown (My University, 2024)
Along with the Americas, Africa is probably the continent where labrets have been used most extensively. Until recently, over a large part of the continent, from the Atlantic to the Indian Ocean, labrets of varied materials and shapes were worn by women and/or men from very diverse populations speaking a wide variety of languages. However, the history of African labrets, which has little interested scholars, remains poorly known. To trace this history, we can rely on two types of evidence: the labrets themselves and the consequences of their use on the teeth. As both types of evidence have their own potential and limitations as clues of the use of lip ornaments, we would expect them to provide complementary information on the ornamental practices of past societies. In practice, however, as shown by the earliest African contexts, they are not always been recognized jointly. This fact is all the more worthy of mention and discussion given that, as things stand at present, archaeological artefacts and anthropobiological traces of their use respectively tell us about different moments in the prehistory of African labrets, where very different processes may have taken place.
Keywords: African Research